Tecnologias digitais na escola: ferramentas potencializadoras de aprendizagem na EJA - Silva, Talita Cardoso Silva e (Universidade Federal do Tocantins, 2022)
Basically the DTIC are understood as a set of equipment and technological applications that generally use the Internet and are differentiated from Information and Communication Technologies (ICT) by the presence of digital. The school is an institution established by society to transmit the cultural heritage of a diversity of knowledge built by society throughout history. In this sense, when we look at the specifics of Youth and Adult Education (YAE), we can understand that it is not limited to schooling. Its history, in the Brazilian reality and also in the Latin American reality, includes the struggle for the right to have access to, to remain in, and to finish schooling with quality. Young people and adults cannot/should not be left aside from the technological transformations that reinvent the way they learn all the time. As a general objective, we sought to understand how the use of Digital Information and Communication Technologies - DTIC can add efficiency to the learning process of EJA students. As methodological procedures, the research has a qualitative approach, of the field research type, and the data analysis was based on Content Analysis. As instruments of information collection, we used online questionnaires with YAE students, teachers and managers of a public school located in a city in Bahia, in addition to the school's Political and Pedagogical Project. The research made it possible to understand that the use of Digital Information and Communication Technologies (DTIC), when properly used in the classroom by the teacher and well oriented regarding their use by YAE students, can contribute to a more efficient teaching and learning process, since knowing well the resources of the technologies used, as well as appropriating them as a teaching methodology allied to the teaching work, can enhance the learning and production of knowledge of students when they get to know new contents and develop reading and writing skills via virtual learning platforms. This study also showed that researching ICT and YAE is important to broaden the debate in educational research regarding the use of these technologies in the classroom, since this subject is still incipient in academic literature.